Methods and introductory results of the Greek national health and nutrition survey - HYDRIA (Epidemiology, Biostatistics, and Public Health, 2022)
Background:  According to a large prospective cohort study (with baseline examination in the 1990s) and smaller studies that followed, the population in Greece has been gradually deprived of the favorable morbidity and mortality indices recorded in the 1960s. The HYDRIA survey conducted in 2013-14 is the first nationally representative survey, which collected data related to the health and nutrition of the population in Greece.Methods: The survey sample consists of 4011 males (47%) and females aged 18 years and over. Data collection included interviewer-administered questionnaires on personal characteristics, lifestyle choices, dietary habits and medical history; measurements of somatometry and blood pressure; and, blood drawing. Weighting factors were applied to ensure national representativeness of results.Results: Three out of five adults in Greece reported suffering of a chronic disease, with diabetes mellitus and chronic depression being the more frequent ones among older individuals. The population is also experiencing an overweight/obesity epidemic, since seven out of 10 adults are either overweight or obese. In addition, 40% of the population bears indications of hypertension. Smoking is still common and among women the prevalence was higher in younger age groups. Social disparities were observed in the prevalence of chronic diseases and mortality risk factors (hypertension, obesity, impaired lipid profile and high blood glucose levels).Conclusion: Excess body weight, hypertension, the smoking habit and the population’s limited physical activity are the predominant challenges that public health officials have to deal with in formulating policies and designing actions for the population in Greece.